Regeneration of complete Glyptostrobus pensilis (Staunton ex D. Don) K. Koch plants from in vitro derived shoots - Thanh, Nguyen Duc; Minh Lua, Dang Thi; Lien, Quach Thi (Academia Journal of Biology, 2012)
Glyptostrobus pensilis (Staunton ex D. Don.) K. Koch is an endangered species that cited in Vietnam and World’s Red Books. In Vietnam, Glyptostrobus pensilis is distributed in two locations of Dak Lak province: about 200 individuals in special use forest of Earal, EaH’Leo district and 30 individuals in Trap Ksor’s special use forest of Krong Nang district. Glyptostrobus pensilis is not only important for botanical science as a living fossil of gymnosperm, but for economic value as well. Therefore, the study on conservation and development of this tree species is a very urgent task. Many attempts to regenerate the tree from the seeds have been failed. So, the vegetative propagation (cutting, grafting and tissue culture) could be a good alternative solution for rapid propagation of Glyptostrobus pensilis. Although, there were some reports on propagation of Glyptostrobus pensilis by tissue culture, but the generation of whole plants in in vitro condition was still limited. In this paper, the regeneration of complete Glyptostrobus pensilis plants from in vitro derived shoots and successful transfer of the plants to the soil are presented. The WP medium with 0.5 mg/l BAP, 0.2 mg/l NAA, 0.2 g/l myo-inositol, 20 g/l sucrose, 2 g/l active charcoal and 8 g/l agar was suitable for shoot propagation. The WP medium supplemented with 0.2 mg/l IBA or NAA did the promotion of root formation, but the root production rate was still low. The pretreatment of in vitro shoots by high concentration of IBA has enhanced the root production rate from in vitro derived shoots up to 5.55%. The results obtained in this study will contribute to the conservation and development of this rare, valuable and endangered tree species.